Solitary Fibrous Tumour of the Pleura: A Case Report - George Rakovich; Maxime Laflamme; Denise Ouellette; Gilles Beauchamp (Canadian Respiratory Journal)
Solitary fibrous tumours of the pleura are rare pleural neoplasms that are distinct from mesothelioma. Most of them are benign, although some behave aggressively; morphological and pathological features are important in distinguishing them from mesothelioma and in predicting clinical behaviour. Solitary fibrous tumours often grow to a large size before causing symptoms, and are characteristically associated with hypertrophic pulmonary osteoarthropathy in up to 20% of cases. In cases of benign lesions, complete resection is usually curative. A case involving a 62-year-old woman who underwent surgical resection of a solitary fibrous tumour of the pleura measuring 25 cm in size is described.